Dose Prediction for Prostate Radiotherapy Planning - Delasalles, Edouard; Vauclin, Remi; Mengin, Elie; Ungun, Baris; Costea, Madalina\\-Liana; Bus, Norbert; Komodakis, Nikos; Fenoglietto, Pascal; Gungor, Gorkem; Paragios, Nikos (ELSEVIER IRELAND LTD, 2024)
Annual Meeting of the European-Society-for-Radiotherapy-and-Oncology (ESTRO), Glasgow, ENGLAND, MAY 03-07, 2024
Keywords: Radiotherapy planning; Dose Prediction